Ginsenoside Rg3 sensitizes hypoxic lung cancer cells to cisplatin via blocking of NF-κB mediated epithelial–mesenchymal transition and stemness. (28th February 2018) - Wang, Jingjing; Tian, Lili; Khan, Muhammad Noman; Zhang, Li; Chen, Qun; Zhao, Yi; Yan, Qiu; Fu, Li; Liu, Jiwei
Abstract: Cisplatin is a first line chemotherapy in lung cancer, but decreased susceptibility may limit its application. In solid tumors, hypoxia alters the microenvironment and is associated with proliferation, metastasis, and drug sensitivity. The hypoxia-induced desensitization of cisplatin is not clearly elucidated. 20 (R)-Ginsenoside (Rg3), the traditional Chinese medicine, is extracted from ginseng and has antitumor activities. In this study, we evaluated if Rg3 is effective in improving cisplatin sensitivity by blocking hypoxia. We found that the inhibition of proliferation potential by cisplatin was reduced in cobalt chloride (CoCl2 )-induced hypoxia in lung cancer cells. Hypoxia caused alterations in epithelial–mesenchymal transition (EMT), which were detected by cellular morphology and EMT protein markers, and in stemness analyzed by spheroid formation and marker molecules. Hypoxia also activated EMT, which was mediated by the nuclear factor κB (NF-κB) pathway, and stemness, and Rg3 inhibited the activation of the NF-κB pathway. Furthermore, Rg3 could increase the sensitivity to cisplatin by inhibiting EMT and stemness in hypoxic lung cancer cells, and this effect was confirmed in vivo . In conclusion, Rg3 may improve the sensitivity of cisplatin in lung cancer therapy. Highlights: Hypoxia reduced cisplatin chemosensitivity in lung cancer cells. Hypoxia induced EMT and stemness mediated by the NF-κB signaling pathway. Rg3 inhibited NF-κB activation in hypoxia in a concentration/time-dependent manner. Rg3 + cisplatin inhibited hypoxia-induced EMT and stemness in vitro and in vivo . This is the first report that Rg3 had an anti-stemness effect.